Application of Fractal Geometry in the construction of antennas: an assessment of activities in context by engineering students - Artigue, Victoria (2023)
This paper presents the students´ perceptions about the implementation of a teachingproposal, based on the application of mathematics, in particular linear algebra applied tofractal antennas. The didactic interest in Fractal Geometry is recent, constituting a relevantproblem, due to its enormous application possibilities. This geometry, very different from theEuclidean geometry, has not yet been widely addressed in Mathematics Education,although it is proposed in the curricula. We applied a 20-item survey to 26 students of a firstyear of engineering career, to gather their opinions. It was found that engineering studentsincreased their motivation and took advantage of the potential of the proposal, byexperiencing mathematics in engineering situations such as fractal antennas.